DEVELOPMENT OF LINGUOCULTURAL COMPETENCES OF A PERSON AS A PEDAGOGICAL PROBLEM (American Journal of Pedagogical and Educational Research, 2024)
This work is devoted to the problem of the development of linguistic and cultural competencies of a person in the context of pedagogical activity. The author explores the importance of developing students' skills and knowledge necessary for effective interaction with representatives of other cultures through language. The methods and approaches that contribute to the development of linguistic and cultural competencies, as well as problems arising in the learning process, are considered. The paper focuses on the role of the teacher in the formation of these competencies among students and offers practical recommendations for the successful solution of this problem.